2020
DOI: 10.46328/aejog.v2i3.60
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Congenital Malformations in Adolescent Pregnancies: A Single Tertiary Center Experience in Turkey

Abstract: Objective: Adolescent pregnancies are more severe and dangerous for both mother and baby than adult pregnancies. Low birth weight, infections, intrauterine growth restriction, sudden infant death syndrome, and death risk are higher in neonates of adolescent pregnant women. Besides, anomalies of central nervous, gastrointestinal, and musculoskeletal systems are also seen frequently. The purpose of this study is to investigate congenital malformations of infants born from adolescent mothers. In this study, malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A substantial percentage of TOF cases were observed with extracardiac abnormalities. [21][22][23] Several previous reports found that the incidence of TOF cases with one or more congenital extracardiac abnormalities was 17-28%. The most common extracardiac anomalies were detected to be genitourinary, musculoskeletal, and gastrointestinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial percentage of TOF cases were observed with extracardiac abnormalities. [21][22][23] Several previous reports found that the incidence of TOF cases with one or more congenital extracardiac abnormalities was 17-28%. The most common extracardiac anomalies were detected to be genitourinary, musculoskeletal, and gastrointestinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal anomalies are detected in approximately 50-60% of spontaneous abortions and 2-4% of all newborns. Fetuses with chromosomal abnormalities are at risk for adverse fetal outcomes, and these abnormalities cause 20% of deaths in the first year of life [1][2][3][4]. Chromosomal abnormalities represent approximately 15% of the major congenital anomalies diagnosed before the age of 1 year in Europe [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to their obstetric and perinatal risks, APs are related to educational, parenting, and mental health problems. [2][3][4][5][6] The dual biological transitions of pregnancy and adolescence might elevate the stress levels and the physical and psychological vulnerability of the person. 7 Also, AP frequently happens within circumstances of risk, which expose adolescent females to various causes of psychosocial trou-ble and difficulties in reaching support and care.…”
mentioning
confidence: 99%